Islamic Education According to Yusuf Al Qardhawi's Perspective in the Manhaj Da'wah Book - Setiawan, Aris; Sa'bani, Moh. Ahyan Yusuf (Program Pascasarjana Pendidikan Islam Universitas Islam Darul Ulum Lamongan, 2023)
Shaykh Yusuf Al-qaradhawi's view of Islamic education emphasizes an inclusive and comprehensive approach. According to him, Islamic education goes beyond the confines of religious studies alone, involving Islamic character building that includes moral aspects, skills, and personal development. Al-Qardhawi asserts the need for harmonization between the goals and means of education so that teaching methods, books, and educators' involvement align, intending to form Muslim individuals who benefit society, self, and the hereafter. In addition, his moderate and inclusive approach embraces knowledge from various fields, placing religious education and general science in a complementary context and contributing to forming a generation with a strong Islamic character